The Role of Hindu Religious Education in Instilling Character Values in the Young Generation in the Digital Era - Sudarsana, I Ketut; Mastini, Gusti Nyoman (Jurnal Penelitian Agama Hindu, 2025)
The development of digital technology in the modern era has a significant impact on the behavior and character of the young generation, both positively and negatively. The emergence of moral crises, declining social ethics, and a lack of role models pose serious challenges in the world of education, especially in shaping students’ character. Hindu religious education has great potential in responding to these challenges through the Dharma teachings, which are rich in ethical and spiritual values. This study aimed to examine in depth the role of Hindu Religious Education in instilling character values in the young generation in the digital era. The method used was a qualitative approach with a literature review technique, which involved examining various sources of Hindu religious literature, educational policies, and relevant previous research results. The results indicated that Hindu Religious Education was capable of instilling character values, such as honesty (Satya), peace (Ahimsa), discipline (Tapa), social responsibility (Yadnya), and spiritual devotion (Bhakti) through an adaptive contextual approach utilizing digital technology. The utilization of digital-based learning media such as Dharma discourse videos, religious e-learning, and Hindu-based interactive applications has been proven to increase student engagement in understanding and internalizing character values. In addition, the involvement of teachers, families, and indigenous communities also strengthened the collective instillation of character values. This study concluded that Hindu Religious Education played a strategic role in building the moral and spiritual character of the young generation. The positive ultilaztion of technology and synergy between educational institutions and the social environment were the key to successfully delivering Hindu character education that was relevant to the challenges of the times.